2016
DOI: 10.1038/srep33798
|View full text |Cite
|
Sign up to set email alerts
|

Polyoxazoline multivalently conjugated with indocyanine green for sensitive in vivo photoacoustic imaging of tumors

Abstract: Photoacoustic imaging, which enables high-resolution imaging in deep tissues, has lately attracted considerable attention. For tumor imaging, photoacoustic probes have been proposed to enhance the photoacoustic effect to improve detection sensitivity. Here, we evaluated the feasibility of using a biocompatible hydrophilic polymer, polyoxazoline, conjugated with indocyanine green (ICG) as a tumor-targeted photoacoustic probe via enhanced permeability and retention effect. ICG molecules were multivalently conjug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 33 publications
(51 reference statements)
2
32
0
Order By: Relevance
“…[ 31 ] The third one is photoacoustic imaging, which could detect highly sensitive and high-resolution photoacoustic signals in deep tissues. [ 32 ] Thus, we speculated that new molecular imaging techniques could be helpful for preoperative diagnosis, therapy, and prognosis estimate in LGMS. Unfortunately, due to the lack of the new molecular imaging system, this patient was not performed these specific examinations before surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[ 31 ] The third one is photoacoustic imaging, which could detect highly sensitive and high-resolution photoacoustic signals in deep tissues. [ 32 ] Thus, we speculated that new molecular imaging techniques could be helpful for preoperative diagnosis, therapy, and prognosis estimate in LGMS. Unfortunately, due to the lack of the new molecular imaging system, this patient was not performed these specific examinations before surgery.…”
Section: Discussionmentioning
confidence: 99%
“…ICG, approved for clinical use by the US Food and Drug Administration, is highly biocompatible and has been widely used for tumor cell imaging. 32 In this study, we evaluated the cellular uptake of nanoparticles through encapsulating ICG using a confocal fluorescence microscope (Figure 2). The results showed that the fluorescence intensity of cells treated with Cet-PEG-PLA-ICG was significantly higher than that of cells treated with PEG-PLA-ICG.…”
Section: Cellular Uptakementioning
confidence: 99%
“…Thermoresponsive POZ derivatives including EtPOZ composed of 2-ethyl-2-oxazoline, IspPOZ composed of 2-isopropyl-2-oxazoline, Isp-PrPOZ composed of 2-isopropyl-2-oxazoline and 2-propyl-2-oxazoline, and PrPOZ composed of 2-propyl-2-oxazoline were synthesized according to previous reports (11,16). The reaction scheme is shown in Figure 2.…”
Section: Synthesis Of Amine-terminated Poz Derivativesmentioning
confidence: 99%
“…Poly (2-alkyl-2-oxazoline) (POZ), an isomeric polypeptide material that can be synthesized via living cationic ring-opening polymerization (8), is garnering attention as a biocompatible and hydrophilic biomaterial for drug delivery (9,10), in addition to the more traditional polyethylene glycol. Recently, we have demonstrated that chemically modified POZ accumulates in tumor tissue via an enhanced permeability and retention effect and is rapidly cleared from the blood after intravenous injection of the probe (11), indicating its usefulness for biomedical applications. Moreover, POZ has a lower critical solution temperature and can self-aggregate above a specific transition temperature (Tt) that is dependent on the oxazoline composition and molecular weight of its polymers (12,13), which can be controlled in a range of 10°C-90°C.…”
mentioning
confidence: 99%